Primary knowledge enhances performance and motivation in reasoning. (August 2018) - Lespiau, Florence; Tricot, André
Highlights: Primary knowledge is used as context for logical reasoning tasks. It increases performance, emotional and cognitive investment. It decreases perceived cognitive load. Presented before secondary knowledge, it has a positive impact on logical responses. Primary knowledge as a context could be a good way to introduce a new topic.